Neonatal versus postneonatal presentation of intestinal malrotation: A retrospective cross-sectional study in a tertiary care hospital at Hyderabad, India - Srinivas Srirampur; Kavimozhy Ilakkiya Poyyamozhy; Thanneeru, Suresh Kumar; Nagarjuna Kumbha (Asian Journal of Medical Sciences, 2022)
Background: Malrotation commonly presents in neonates with bilious vomiting. It may also present in post neonatal age group with vague symptoms such as chronic abdominal pain, vomiting, and failure to thrive. These indistinct symptoms also result in delay of diagnosis. Aims and Objectives: This study is done with an objective to know whether age of presentation in malrotation determines morbidity and mortality. Materials and Methods: This is a retrospective study conducted in Gandhi medical college and Hospital, Hyderabad, from 2017 to 2020, based on the records of 50 patients who were diagnosed to have malrotation. The differences in clinical presentations, diagnosis, management, and outcomes were analyzed with respect to age. Results: Children who presented in neonatal period had classical symptoms (P<0.00001) and early diagnosis (P<0.0239). Children who presented later (>1 month of age) had higher incidence of atypical symptoms (P<0.00001) and delay in diagnosis (P<0.0239) compared to neonatal age group. Plain X-ray abdomen is readily diagnostic in neonatal age group (P<0.0004) and diagnosis was confirmed by contrast study, whereas in older children, plain abdomen X-ray findings were not always distinct and most of them needed contrast series to reach definitive diagnosis. The incidence of bowel gangrene and mortality was not statistically significant (P value of 1) between neonatal and post neonatal groups. Conclusion: In post neonatal age group, lack of classical presentation may lead to difficulty in diagnosing malrotation, but may not have significant difference in terms of morbidity and mortality. Considering malrotation early in differential diagnosis leads to timely intervention even in older age group children.